Bloqueio infiltrativo incisional com bupivacaína em cadelas submetidas à ovariohisterectomia por celiotomia ou videoassistida com dois portais - Martins, Leticia Reginato (2017)
This study aimed to investigate the use of local infiltrative anesthesia with 0.5% bupivacaine in surgical incision site as part of a multimodal analgesic approach in dogs submitted to ovariohysterectomy (OVH) by celiotomy or video-assisted by two-port. Twenty-eight adult (2.08 ± 1.45 years) and healthy bitches, weighing 12.67 ± 1.94 kg, with aptitude confirmed by clinical and laboratory tests were selected. Dogs were pre-medicated with acepromazine (0.05mg.kg-1, IM), induced and maintained in general anesthesia with propofol (4mg.kg-1, IV) and isoflurane vaporized in 100% oxygen, respectively. Intraoperative analgesia was promoted with fentanyl in continuous infusion (20μg.kg -1.hour-1), preceded by a loading dose (2,5μg.kg-1, IV). Dogs were divided into four groups: control group celiotomy (CC, n = 7), blocking group celiotomy (BC, n = 7), control video-assisted group (CV) and blocking video-assisted group (BV). In the blocked groups (BC and BV), bupivacaine (2mg.kg-1) was administered subcutaneously in the incision line or port entry sites. Control groups received 3 ml of saline solution at the same sites. Meloxicam (0.2mg.kg-1) administered at the end of the surgery with the combination of metamizole sodium and Hyoscine N-butyl bromide every 8 hours for 2 days. Postoperative pain was evaluated by three evaluators blinded to surgery and treatment established, using Melbourne Pain Scale and visual analogue scale. Pain was assessed hourly in the first 8 hours and, then, at 12, 18, 24, 36 and 48 hours post-extubation. Glycemia and serum cortisol were evaluated too. Rescue analgesia was administered to one animal in CV after one hour postoperative, while seven dogs in CC received additional analgesia in the first two hours postoperative and was not required by any of the animals that received anesthetic block (BC and BV). Statistical analysis suggested that the anesthetic infiltrative blockade performed with 2,0mg.kg-1 bupivacaine was efficient in promoting postoperative comfort when used in both celiotomy and video-assisted OVH..